Weissella confusa: problems with identification of an opportunistic pathogen that has been found in fermented foods and proposed as a probiotic - Fairfax, Marilynn R.; Lephart, Paul R.; Salimnia, Hossein (Frontiers in Microbiology, 2014)
Weissella confusa is found in fermented foods and has been suggested as a probiotic, but also causes sepsis and other serious infections in humans and animals. The incidence of human infections is underestimated partly due to confusion with viridans streptococci and partly due to difficulty making a definitive identification, even if the organism is recognized to belong to another genus, owing to the inability of commercial organism systems to identify it. We report our experiences identifying W. confusa isolated from two immune-compromised patients, both of whom developed sepsis with this organism. Two MicroScan gram positive combination panels, could not identify the organism because they did not have W. confusa in their data bases, but did not provide a false identification. Other laboratorians have reported failure to identify or false identifications of W. confusa with other commercial systems. W. confusa is in the data base of the RapID™ Str panel (Remel), which gave three incorrect, high probability results (≥95%). 16S rDNA sequencing identified the isolates as W. confusa. Maldi-Tof, performed by two of our reference laboratories, also correctly identified both isolates. Use of W. confusa as a probiotic should be approached with caution because its true incidence as an opportunisitic pathogen is unknown.